keterkaitan Pancasila sebagai dasar negara dalam kehidupan masyarakat modern - Az-zahra, Aiyla Falisha (Maliki Interdisciplinary Journal, 2025)
Pancasila, as an open ideology, possesses universal values that serve as the foundation and unifier of social life in Indonesia. As the state foundation, Pancasila contains norms that are inherent and have developed within society for a long time, formulated to meet the needs of a pluralistic and dynamic nation. In the modern era, the currents of globalization, technology, and social transformation present challenges such as materialism, consumerism, and the erosion of national identity, which demand the relevance of Pancasila as a guide to life. The five principles of Pancasila continue to serve as a moral and ethical foundation in modern life, ranging from strengthening religiosity, ethics of digital interaction, maintaining unity, democratic culture, to social justice. The implementation of Pancasila in education, governance, socio-cultural fields, and the role of the younger generation is crucial to strengthening nationalism and facing the changes of the times. Through character education, just policies, and active participation of the youth, Pancasila remains capable of being a dynamic ideology that addresses the challenges of the modern era and realizes the aspirations of the Indonesian nation towards a just, prosperous, and civilized society